The chronostratigraphic method is unsuitable for determining the start of the Anthropocene. (June 2019) - Edgeworth, Matt; Ellis, Erle C; Gibbard, Philip; Neal, Cath; Ellis, Michael
This paper responds to and supports the earlier 'Three Flaws' paper by William Ruddiman (this journal, 2018). It builds upon his critique of the method used by the Anthropocene Working Group in determining the start date of the Anthropocene. While chronostratigraphy is acknowledged as the best means of establishing a framework for the division of deep time – on geological timescales of millions of years – it is argued that the method is unsuitable for use on archaeological and historical timescales. Close proximity in time between the chronostratigraphic observer and the stratigraphic boundary in question renders the placement of a precisely defined, globally synchronous timeline onto highly time-transgressive evidence inappropriate on these scales of analysis. Application of the method hinders rather than helps understanding of the role of human impact on Earth System change; it leads to a loss of the bigger picture and to relative neglect of the crucial evidence provided by humanly modified ground – the missing strata in most chronostratigraphic accounts of the Anthropocene start. A more ground-up approach is called for. Recognition of humans as geological agents needs to be accompanied by recognition of the distinctive traces of human agency in the ground, which are unprecedented in the stratigraphic records of earlier geological time periods.